2021
DOI: 10.1002/ajhb.23561
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal socioeconomic, psychosocial and seasonal factors, infant characteristics and human milk cortisol concentrations

Abstract: Objectives: Glucocorticoids are one component of human milk (HM) potentially affecting offspring development. Previous studies have identified various maternal, obstetric and socioeconomic characteristics that are associated with HM cortisol concentration but the literature is still scarce concerning these determinants in human populations. We aimed to identify which factors are linked with HM cortisol concentration at 2 months postpartum.Methods: We analyzed data from 340 lactating Finnish mothers using ordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 48 publications
2
23
1
Order By: Relevance
“…Previous studies, including one from our group, have shown that GC levels in human milk follow a typical diurnal pattern, mirroring GC levels in saliva [ 7 , 8 ]. There is some evidence suggesting that GCs through human milk may be important for metabolism, neurodevelopment and immunity [ 9 ], although the evidence is not unequivocal [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies, including one from our group, have shown that GC levels in human milk follow a typical diurnal pattern, mirroring GC levels in saliva [ 7 , 8 ]. There is some evidence suggesting that GCs through human milk may be important for metabolism, neurodevelopment and immunity [ 9 ], although the evidence is not unequivocal [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The GC composition in human milk may be influenced by various factors, including maternal stress, weight, educational status and parity [ 9 , 11 , 12 ]. Studies addressing the relation between maternal stress and GC levels in human milk are scarce [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to maternal melatonin, cortisol in breast milk circulates from the maternal plasma and follows the same diurnal variation found in plasma and saliva [ 119 , 135 ]. Human milk cortisol levels vary based on season and psychological distress [ 136 , 137 ]. Data from rodent studies have established that ingested glucocorticoids diffuse from the neonatal intestines into the plasma and brain [ 138 ].…”
Section: Factors Influencing Circadian Development In Infancymentioning
confidence: 99%
“…Many mothers with postpartum depression have poor parenting and childcare skills due to low maternal attachment and sensitivity levels, which are acknowledged risk factors for impairment in cognitive, socioemotional, and behavioural development in children 19,22‐25 . Psychosocial (household income, educational attainment, and partner support for childcare) and personal factors (maternal age, parity, drinking and smoking habits, child's sex and development and a history of depression) have been identified as risk factors for postpartum depression 26‐30 . Although maternal postpartum depression directly affects child health and behavioural development, 19,22‐25 the impact of maternal postpartum depression on child toothbrushing behaviour remains unknown.…”
Section: Introductionmentioning
confidence: 99%